Overview Of Housewife's Income In Pig Fattening Businesses In Makale District Tana Toraja District - Nurlaela; Aylee Christine Alamsyah Sheyoputri; Faidah Azuz; Ahfandi Ahmad (Tarjih : Agribusiness Development Journal, 2026)
This research analyzes the pig fattening business in Makale District, Tana Toraja Regency. The background to this research is the critical role of pig-fattening companies as a source of income for local communities. This research identifies factors such as breeder characteristics, maintenance systems, capital analysis, and revenue as indicators of business success. The method used is direct observation and interviews with breeders who, in this case, have the status of homemakers and were selected at simple random. The data collected consists of primary data, including the respondents' identity and business management, and secondary data from related agencies. Descriptive analysis describes business maintenance management, while income analysis is carried out by calculating total costs and revenues. The research results show that most breeders have quite a long experience, with relatively large production amounts on a household scale. Overall, this fattening business shows a net income of IDR. 237,233,000.00 or IDR. 1,040,495.00/head. In conclusion, the pig fattening business in Makale District, Tana Toraja Regency, has excellent and profitable prospects for farmers, mainly if managed efficiently and sustainably.